A Poetics of Social Work: Personal Agency and Social Transformation in Canada, 1920-1939 - Marshall, Dominique (Labour / Le Travail, 2004)
The article reviews the book, "A Poetics of Social Work: Personal Agency and Social Transformation in Canada, 1920-1939," by Ken Moffatt.